2021
DOI: 10.1186/s13018-021-02295-8
|View full text |Cite
|
Sign up to set email alerts
|

Patella resurfacing during total knee arthroplasty is cost-effective and has lower re-operation rates compared to non-resurfacing

Abstract: Background The decision to resurface the patella as part of total knee arthroplasty may be influenced by the surgeon’s preference, education, training, tradition and geographic location. Advocates for non-resurfacing or selectively resurfacing may claim no difference in patient reported outcomes, and that resurfacing is associated with increased risks such as extensor mechanism injury or malalignment, problems with the design of the patella component and technical issues intraoperatively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 64 publications
0
8
0
3
Order By: Relevance
“…Diversos autores han descrito los beneficios de la resuperficialización de la rótula en los resultados funcionales y las tasas de revisión después de un RTR. 7,9,10 Quienes se oponen a este procedimiento justifican su conducta en las potenciales complicaciones asociadas a este paso adicional, como la inestabilidad, la fractura, el desgaste del polietileno, el pinzamiento de tejidos blandos y la osteólisis. 11,12 Por ejemplo, Schiavone Panni y cols.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Diversos autores han descrito los beneficios de la resuperficialización de la rótula en los resultados funcionales y las tasas de revisión después de un RTR. 7,9,10 Quienes se oponen a este procedimiento justifican su conducta en las potenciales complicaciones asociadas a este paso adicional, como la inestabilidad, la fractura, el desgaste del polietileno, el pinzamiento de tejidos blandos y la osteólisis. 11,12 Por ejemplo, Schiavone Panni y cols.…”
Section: Resultsunclassified
“…informaron que la resuperficialización de la rótula se puede considerar una intervención costo-efectiva, y que tiene una baja tasa de revisión, aunque sus resultados funcionales son equivalentes entre pacientes sometidos a un RTR con resuperficialización y sin este procedimiento. 9 Por lo anterior, el objetivo de este estudio fue comparar los resultados funcionales del RTR con resuperficialización de la rótula o sin resuperficialización a los dos años de seguimiento.…”
Section: Introductionunclassified
“…The strongest association between prosthesis factors and revision was shown in the analysis of patellar component use and revision for patellar reasons, where not using a patellar component showed much higher odds for revision for these diagnoses. Although some controversy may remain around function and pain relief regarding patellar component use ( 40 ), there seems less doubt that using a patellar component leads to a lower rate of revision for this reason ( 41 ). The finding that MB prostheses also showed higher odds for revision for patellar reasons is contrary to a study from the New Zealand Joint Registry that found fixed-bearing PS prostheses had a higher rate of secondary patellar resurfacing than mobile-bearing designs ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…When indicated, patellar resurfacing has been documented to be cost-effective with a 4.6% reduction in the absolute risk of reoperation and a 13.85% reduction in the absolute risk of postoperative anterior knee pain in comparison to nonresurfacing [ [34] , [35] , [36] , [37] ]. Despite these benefits, patellar resurfacing has also been associated with complications including maltracking, implant loosening, dislocation, osteonecrosis, extensor mechanism injury, and fracture [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%